Promises in Death - Robb, J. D., 1950- (London Piatkus, 2009)
Every cop gets angry when a police officer is killed. And Lieutenant Eve Dallas is no exception. But Amarylis Coltraine was also in a relationship with one of Eve's colleagues, so after Eve has delivered the terrible news to him, she throws every resource she has into finding the killer. When she finds a link to the son of a criminal she and her husband Roarke had put behind bars, the case heats up even further. Alex Ricker was romantically involved with Amarylis ? did she leak information to him and then have a change of heart? Eve puts herself in danger to get to the truth ? but she can't prevent another death before she learns who betrayed both the criminal's son and the police officer he loved..." -- Publisher description.
Keywords: Policewomen -- Dallas, Eve (Fictitious character) -- Police murders